Antiplatelet Therapy in Myocardial Bridge: Insights From the RIALTO Registry - Renzo Laborante; Giuseppe Ciliberti; Gaetano Rizzo; Francesco Canonico; Donato Antonio Paglianiti; Fabio Casamassima; Attilio Restivo; Domenico Cicchella; Francesco Burzotta; Carlo Trani; Cristina Aurigemma; Mattia Galli; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Myocardial bridge (MB) is a frequent coronary artery anomaly. The aims of this study are to describe the use of antiplatelet therapy (APT) in a cohort of patients with MB and assess its impact on ischemic and bleeding events. Methods The RIALTO (Myocardial Bridge Evaluation Towards Personalized Medicine) registry (ID: NCT05111418) is an ambispective multicenter observational registry, enrolling patients with a clinical indication to coronary angiography and evidence of MB. The present analysis included patients with MB without any preexisting indication for APT/anticoagulant therapy according to guidelines. Patients were categorized into 2 groups: single APT or no APT based on discharge prescriptions. The primary end point was the time to first occurrence of net adverse clinical events, defined as a composite of cardiovascular death, nonfatal myocardial infarction, unplanned or elective coronary angiography, ischemic cerebrovascular events, and any bleeding. Results Out of 486 enrolled patients with MB, 221 (mean age: 60 years, 66% male) were included in this analysis. One hundred and forty‐one patients (64%) received single APT. At a median follow‐up of 1661 days, patients with MB receiving single APT had a higher rate of net adverse clinical events (adjusted hazard ratio [aHR], 6.2; P=0.03), mainly driven by a higher rate of minor bleeding events (aHR, 10.58; P=0.02), with no difference regarding ischemic events. Results were consistent after 1:1 propensity‐score matching sensitivity analyses. Conclusions The prescription of single APT is common in patients with MB, and it seems to be associated with an increased risk of bleeding, in the absence of a beneficial effect on ischemic events.